ANALISIS PENGARUH PENGALAMAN AUDIT, SKEPTISME PROFESIONAL, RED FLAGS, DAN TEKANAN ANGGARAN WAKTU TERHADAP KEMAMPUAN AUDITOR DALAM MENDETEKSI KECURANGAN - Eriyanti, Eriyanti; Widaryanti, Widaryanti; Mohklas, Mohklas (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2022)
This study aims to analyze the effect of audit experience, professional skepticism, red flags and time budget pressure on the ability to detect fraud in KAP Semarang City. The population in this study were auditors at KAP in Semarang City. Data collection was carried out using convenience sampling method and the number of respondents was 64 respondents. The type of data used is primary data. This study uses a questionnaire in data collection. The test technique used is validity test, reliability test, classical assumption test includes normality test, multicollinearity test, and heteroscedasticity test. Hypothesis testing in this study uses multiple linear regression analysis and hypothesis testing with the help of SPSS version 21. The results of this study indicate that audit experience, professional skepticism, red flags have a positive and significant effect on the ability to detect fraud. Meanwhile, time budget pressure does not have a positive effect on the ability to detect fraud.Keywords: Audit Experience, Professional Skepticism, Red Flags, Time Budget Pressure and Fraud Detection Ability.